2002
DOI: 10.1038/sj.onc.1205913
|View full text |Cite
|
Sign up to set email alerts
|

Human melanocortin 1 receptor (MC1R) gene variants alter melanoma cell growth and adhesion to extracellular matrix

Abstract: Pigmentation is a significant determinant of individual susceptibility to cutaneous melanoma, with fair skinned subjects at highest risk of developing this neoplasm. Melanocortin 1 receptor (MC1R) gene variants alter pigment synthesis in vivo, and are causally associated with red hair and fair skin in humans. MC1R variants are more frequent in subjects with melanoma, and increase the risk of developing this tumour in sporadic and familial cases. MC1R variants may predispose to melanoma as a result of alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 60 publications
1
44
0
Order By: Relevance
“…However, not all studies are in agreement (Ichii-Jones et al, 1998). a-Melanocyte-simulating hormone has been demonstrated to affect melanoma growth and attachment to ECM proteins in cells with wild-type MC-1, but not in cells transfected with polymorphic variants (Robinson and Healy, 2002). The current study provides strong evidence to suggest that two out of three human cell lines that possessed MC-1R polymorphisms, which gave a loss of cAMP response to MSH, resulted in cells that failed to respond to MSH with any reduction of invasion or protection against proinflammatory cytokine attack.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not all studies are in agreement (Ichii-Jones et al, 1998). a-Melanocyte-simulating hormone has been demonstrated to affect melanoma growth and attachment to ECM proteins in cells with wild-type MC-1, but not in cells transfected with polymorphic variants (Robinson and Healy, 2002). The current study provides strong evidence to suggest that two out of three human cell lines that possessed MC-1R polymorphisms, which gave a loss of cAMP response to MSH, resulted in cells that failed to respond to MSH with any reduction of invasion or protection against proinflammatory cytokine attack.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a-MSH to reduce TNF-astimulated NF-kB activity (and oxidative stress) in keratinocyte and melanoma lines (Haycock et al, 1999(Haycock et al, , 2000, suggesting protection of the epidermis from inflammatory and oxidative stresses. In addition, B16 melanoma cells respond to a-MSH with inhibition of growth and reduced adhesion (Robinson and Healy, 2002).…”
mentioning
confidence: 99%
“…Case control, kindred and population studies have demonstrated that, in general, two variant MC1R alleles result in red hair whereas a single variant allele gives rise to fairer skin type (17)(18)(19)(20)(21)(22). Cell transfection assays and transgenic mouse work have indicated that a number of the variant receptors, in particular the Arg151Cys, Arg160Trp, and Asp294His variants, which are frequently associated with red hair and fair skin, are significantly functionally compromised in their ability to signal intracellularly via cAMP, leading to a lighter/phaeomelanic pigmentation phenotype (23)(24)(25). It is therefore possible that human MC1R variants could have consequences on the anti-inflammatory and/or immunomodulatory actions of ␣MSH in humans, especially in cases where the monocyte/macrophage plays an important role.…”
Section: ␣-Melanocyte-stimulating Hormone Suppresses Antigen-induced mentioning
confidence: 99%
“…MC1R is also expressed by melanocytes in the skin, where it plays a central role in human pigmentation. MC1R variants have profound effects on human pigmentation, causing red hair and fair skin phenotypes as a result of the significantly reduced ability of variant receptors to signal via cAMP (18,20,(22)(23)(24)(25). To investigate whether variability in ␣MSH-induced suppression of SK/SD-induced lymphocyte proliferation between subjects was due to genetic variability at the MC1R locus, we extended the study population to include a total of 26 subjects.…”
Section: Suppression Of Sk/sd-induced Lymphocyte Proliferation Is Unrmentioning
confidence: 99%
“…Because skin pigmentation is primarily regulated by the MC1R, its gene is considered a susceptibility gene for melanoma (40).…”
Section: Role Of Melanin In Photoprotection Of the Skinmentioning
confidence: 99%